EFFECT OF SOWING DATE AND SEEDING RATE ON BREAD WHEAT YIELD AND TEST WEIGHT UNDER MEDITERRANEAN CONDITIONS - Costa, Rita; Pinheiro, Nuno; Almeida, Ana Sofia; Gomes, Conceiçã o; Coutinho, José; Coco, Joã o; Costa, Armindo; Maçãs, Benvindo (Emirates Journal of Food and Agriculture, 2017)
Yield and test weight are attributes of particular economic importance in wheat production systems and are strongly affected by environmental conditions. This study was conducted to determine the effects of sowing date and seeding rate on grain yield and test weight of fifteen bread wheat varieties and five advanced lines from Portuguese Wheat Breeding Program (Plant Breeding Station, Elvas, Portugal) under irrigated Mediterranean systems. Field experiments were conducted at two locations of Southeast Portugal, during 2011/2012 growing season. Two seeding rates were compared (200 and 350 seeds.m?2) in two different sowing dates in each location. Results showed that sowing date and seeding rate affects yield and test weight under irrigation field conditions, for Mediterranean region of Southeast Portugal, but only sowing date had significant effects among the varieties. At Elvas, higher yield was obtained with the 2nd sowing date (21 December) for most of the varieties studied. In opposite, in Beja trials, the highest values for yield were found when varieties were sown earlier (1st sowing date - 26 October). Test weight had a similar performance in the two sites, though top values for this trait were found with the 1st sowing date. Comparing the results obtained in the two studied locations, Beja showed, for the majority of the varieties, 3t/ha higher average yield than El